Pengaruh Skeptisme Profesional, Beban Kerja dan Tekanan Waktu Terhadap Kemampuan Auditor Mendeteksi Kecurangan (Fraud) Pada Kantor Akuntan Publik Batam - Tesa Granita Mandalika; Viola Syukrina E Janrosl (LPPM Universitas Putera Batam, 2023)
This research was conducted with the aim of knowing how much influence Professional Skepticism, Workload and Time Pressure have on the auditor's ability to detect fraud at the Batam Public Accounting Firm. This study used an analytical method, which is quantitative data analysis and processed using SPSS version 25. The type of data used in this study was primary data in the form of a questionnaire that was measured using a interval scale. The research population is all junior auditors, seniors, managers and partners working at the Batam Public Accounting Firm who are registered in the Directory of the Indonesian Institute of Public Accountants. The research sample used a purposive sampling technique with population 92 and total sample of 70 respondents. Partially, professionalskepticism obtained results that did not have a significant effect on the auditor’s ability to detect fraud, while workload and time pressure obtained results that had a significant effect on the auditor’s ability to detect fraud. Professional skepticsm, workload and time pressure take effect simultaneously. Based on the test for the coefficient of determination, the result is 68.6%, meaning that the contribution of the percentage of Professional Skepticism, Workload and Time Pressure is 68.6% and external variable factors are 31.4%.